Nonnative be like native speakers: The phonological processes of characters’ English pronunciation in Black Panther movie - Ambalegin Ambalegin (Journal of Applied Studies in Language, 2022)
This study aimed at investigating the English phonological process of characters’ pronunciation while pronouncing the English words in the Black Panther movie. The characters of this movie used the dialect of isiXhosa which is spoken widely in Southern Africa when speaking English. The characters developed the English or they signed phonological disorder. This study was researched qualitatively by using Lass’ theory of phonological process. This study is concerned with assimilation, dissimilation, deletion, and insertion. The result of this study identified that regressive assimilation, progressive assimilation, reciprocal assimilation, aphaeresis, syncopation, apocopation, prothesis, and epenthesis existed. Paragoge and dissimilation were not developed. Aphaeresis showed the highest number of occurrences. Mostly the phonemes arose in /h/ /ɾ/ /j/ /k/ /d/ /t/ /n/, /ð/, /θ/, and /æ/, /ɜ:/, /ə/. /ɾ/ was produced with quick and strong vibration in a syllable, and it was solely deleted in the coda of a syllable, /h/ was deleted by other consonant, the mutual consonants /t/ and /j/ created /ʧ/ and /d/ and /j/ created /dʒ/, /ð/ and /θ/ converted to /d/ and /t/, and schwa converted to /ʌ/. Aphaeresis deletion constructed English contraction. Some phonological process phenomena did not corroborate the Lass’ theory. The phonological process occurred in non-native English speakers due to the influence of L1 pronunciation on L2 pronunciation.